Leadership, organizational culture, and education–training as joint drivers of lecturer–staff performance: Evidence from a nonprofit higher-education institution in Indonesia - Rambe, Kamarul Zaman (Journal of Economics and Business Letters, 2025)
This study examines how leadership, organizational culture, and education–training jointly shape lecturer–staff performance in a nonprofit Indonesian higher-education institution (STIMA KOSGORO). Using a cross-sectional census of all personnel (N = 60; permanent and non-permanent lecturers and staff), we administered context-tailored Likert scales with strong psychometrics (α: leadership .956; culture .947; training .950; performance .931). Assumption checks supported parametric inference. Simple regressions showed that leadership (r = .698; R² = .488), organizational culture (r = .579; R² = .335), and education–training (r = .679; R² = .460) each significantly predicted performance (p < .05). In the multiple regression, all predictors remained significant and together explained 68% of performance variance (R = .825; R² = .680; leadership t = 3.444; culture t = 3.388; training t = 4.487). Substantively, leadership behaviors that clarify roles, coach, and ensure fair consequences produce the steepest returns; culture converts those behaviors into stable routines when rewards align with the outcomes the institution values; and training yields measurable gains when post-training transfer is enforced. We recommend codifying standards and reward rules, institutionalizing leader routines (weekly 1:1s, fast feedback, monthly SOP stand-ups), and tying every training to a 30-day application project to lock in capability gains. These actions are expected to raise performance while preserving fairness and morale in resource-constrained academic settings. Findings extend SHRM and culture–performance evidence to a nonprofit HEI context and offer a pragmatic roadmap for execution.